Elastic moduli of multiblock copolymers in the lamellar phase - Thompson, R. B.; Rasmussen, Kim; Lookman, T. (AIP Publishing, 2004)
We study the linear elastic response of multiblock copolymer melts in the lamellar phase, where the molecules are composed of tethered symmetric AB diblock copolymers. We use a self-consistent field theory method, and introduce a real space approach to calculate the tensile and shear moduli as a function of block number. The former is found to be in qualitative agreement with experiment. We find that the increase in bridging fraction with block number, that follows the increase in modulus, is not responsible for the increase in modulus. It is demonstrated that the change in modulus is due to an increase in mixing of repulsive A and B monomers. Under extension, this increase originates from a widening of the interface, and more molecules pulled free of the interface. Under compression, only the second of these two processes acts to increase the modulus.
Copyright (2004) AIP Publishing. This article may be downloaded for personal use only. Any other use requires prior permission of the author and AIP Publishing. The following article appeared in Journal of Chemical Physics 120 and may be found at http://dx.doi.org.proxy.lib.uwaterloo.ca/10.1063/1.1643899
Keywords: multiblock copolymers; self-consistent field theory; elastic moduli